Peran pendidikan agama dalam membentuk karakter peserta didik: Studi perpustakaan di era digital - Agustina, Rika Agustina (Maliki Interdisciplinary Journal, 2026)
The development of digital technology has had a significant impact on many aspects of education, including students’ behavior and character. Easy access to information through the internet and social media provides great opportunities to support learning, improve students’ knowledge, and help them become more independent. However, besides its benefits, digital technology also brings negative effects, especially related to the decline of moral values, ethics, and students’ sense of responsibility in using digital technology. Exposure to negative content such as hoaxes, hate speech, and the misuse of digital media can influence students’ attitudes and behavior if it is not balanced with strong character education. This condition shows the importance of religious education as a foundation for building students’ character in the digital era. Religious education is expected to instill moral and spiritual values that guide students in their actions and behavior in the midst of technological development. Therefore, this study aims to examine how religious education shapes students’ character in the digital era. This research uses a literature review method by analyzing relevant sources, including academic books, journal articles, and official documents related to religious education, character education, and digital technology. The data are analyzed using a descriptive-analytical approach to gain a comprehensive understanding. The findings show that religious education plays an important role in developing character values such as religiosity, honesty, responsibility, discipline, tolerance, and ethical behavior in using digital technology. Religious education not only provides religious knowledge but also helps shape students’ attitudes and behavior so that they can use technology wisely, critically, and responsibly. Therefore, developing students with strong character is very important in the digital era.